Acute Lymphoblastic Leukemia Presenting Initially as Spinal Cord Compression: When Chemotherapy Alone Is Enough - Albert Jang; Kallie N. Kram; Scott N. Berger; Mahmoud R. Gaballa; Lee B. Lu; David R. Dunaway; Courtney N. Miller-Chism (Case Reports in Medicine)
Spinal cord compression (SCC) is a rare initial presentation and complication of acute lymphoblastic leukemia (ALL) with nearly all reported cases occurring in the pediatric population. We report a 38-year-old previously healthy man who presented with acute on chronic lower back pain, gait instability, urinary retention, and severe thrombocytopenia. Radiologic examination revealed two soft tissue masses of the thoracic spine associated with compression fractures causing spinal canal narrowing and cord compression. Bone marrow biopsy confirmed the diagnosis of ALL. Immediate initiation of high-dose corticosteroids and systemic chemotherapy resolved the patient’s symptoms without radiation therapy or surgical intervention. After two courses of chemotherapy, the patient achieved complete remission in the bone marrow. Rapid administration of chemotherapy alone in this case resulted in a complete resolution of SCC. Given the rarity of this complication in adults, no standardized treatment has been established. The success of this case recommends chemotherapy as the initial management of SCC in chemotherapy-naïve ALL.